Study of quality of cows milk treated bay leaf teat dipping in Tegal Mandiri Farmer - Wihansah, Rifa Rafi'atu Sya'bani; Purwanti, Maya; Wahyuningsih, Wahyuningsih; Harry, Harry (Jurnal Ilmu Peternakan Terapan, 2024)
The aim of this study was to examine the quality of milk including microbiological, chemical properties and detection of subclinical mastitis resulting from the application of bay leaf solution as a natural antiseptic. Application of bay leaf solution was conducted on dairy cows at Tegal Mandiri Farmer Group for 28 days. The parameters observed include microbiological and chemical quality including Total Plate Count (TPC), Staphylococcus aureus contamination, Escherichia coli contamination, fat, protein, lactose content, density and freezing point. Subclinical mastitis was detected using the Draminski Mastitis Detector to see the electrical resistance value of the milk. The results showed that the milk resulting from the application of teat dipping with bay leaf solution had microbiological qualities including Total Plate Count and S. aureus population which met the standards with a TPC population of 4.70 log CFU/ml and S. aureus 0.91 log CFU/ mL, but the E. coli population did not meet the standards. Application of teat dipping with bay leaf solution can reduce the population of S. aureus. Chemical quality in the form of fat content, protein, specific gravity, lactose and freezing point is in accordance with standards. An electrical resistance value of >300 indicates that the milk is of high quality, healthy and has a low incidence of mastitis.